A review on adult pragmatic assessments - Sobhani Rad, Davood (Iran J Neurol, 2014)
Pragmatics is defined as appropriate use of language either to comprehend ideas or to interact in social situations effectively. Pragmatic competence, which is processed in the right hemisphere, comprises a number of interrelated skills that manifest in a range of adaptive behaviors. Due to the widespread influence of language in communication, studying pragmatic profiles, by developing appropriate tools, is of importance. Here, a range of pragmatic theories and assessment instruments available for use in adult patients is reviewed.